The impacts of human development, technology development and globalization to the economic development in Singapore - Eddie, Chang Li Jing (Universiti Malaysia Sarawak, (UNIMAS), 2022)
This study aims to investigate the impacts of human development, technology development and globalization to the economic development in Singapore. The time frame covered by this study is from year 1994 to 2018, giving 25 observations. The test that have employed in this study included Augmented Dickey-Fuller (ADF) Test, Phillips-Perron (PP) Test, Johansen and Juselius Cointegration Test and Granger Causality Test. The empirical results show that there were no long-run relationship among the variable used in this study. Besides that, the Granger Causality Test have displayed that there were multiple unidirectional causality between the variables which were from globalization to technology development, from technology development to economic development and from economic development to human development. In additional, only one out of three independent variables, which was technology development have a causal relationship with economic development.